A TECHNICAL GLANCE ON SOME COSMETİC OİLS - Kenan Yildirim; A. Melek Kostem (European Scientific Journal, ESJ, 2014)
The properties of molecular structure, thermal behavior and UVA protection of 10 types of healthy promoting oils which are argania, almond, apricot seed, and jojoba, wheat germ, and sesame seed, avocado, cocoa, carrot and grapes seed oils were studied. FT-IR analysis was used for molecular structure. DSC analysis was used for thermal behavior and UV analysis was used for UV, visible and IR light absorption. Molecular structure and thermal behavior of avocado and cocoa are different from the others. Contrary to the spectra of avocado and cocoa on which the peaks belongs to carboxylic acid very strong, the spectra of the others do not involve carboxylic acid strong peaks. Almond, wheat germ and apricot seed oil absorb all UVA before 350 nm wave length. The UV protection property of grapes seed and cocoa is very well. Protection of wheat germ, almond and apricot seed oils to UVA is well respectively. Absorption of IR rate change from 7% to 25% for carrot, apricot seed, wheat germ, argania, avocado and grapes seed respectively.